2011
DOI: 10.3855/jidc.1807
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and serological assessment of parvovirus B19 infections among sickle cell anemia patients

Abstract: Introduction: Parvovirus B19 is a cause of hemolysis and red blood cell aplasia in patients with sickle cell anemia. The present study aimed to assess parvovirus B19 infection among sickle cell anemia patients. Methodology: All patients (n = 138) included in the study were sickle cell anemia patients. Blood donors were used as a control group. Assessment of parvovirus B19 antibodies and viral DNA was performed using established methods of detection and B19 recomBlot assay. Results: Detectable levels of parvovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…Therefore, our data and the three recent epidemiological data reported in Nigeria suggest a possible variation in parvovirus b19 activity in different parts of the country. Similar scenarios with anti-parvovirus b19 IgM prevalence rates ranging from 3.9% to 11.1% have been reported in Saudi-Arabia, USA and Tunisia[24],[25],[27] in the setting of SCA. Furthermore, in other target populations such as blood donors, healthy adults, patients with other hemolytic disorders, cancer patients and HIV patients, variations in the prevalence and incidence of parvovirus b19 infections have also been reported in many countries of the world[28][38] ( Table 8 ).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Therefore, our data and the three recent epidemiological data reported in Nigeria suggest a possible variation in parvovirus b19 activity in different parts of the country. Similar scenarios with anti-parvovirus b19 IgM prevalence rates ranging from 3.9% to 11.1% have been reported in Saudi-Arabia, USA and Tunisia[24],[25],[27] in the setting of SCA. Furthermore, in other target populations such as blood donors, healthy adults, patients with other hemolytic disorders, cancer patients and HIV patients, variations in the prevalence and incidence of parvovirus b19 infections have also been reported in many countries of the world[28][38] ( Table 8 ).…”
Section: Discussionsupporting
confidence: 81%
“…Therefore, the presence and absence B19 DNA positivity in the anti-parvovirus B19 IgM seropositive samples screened are indicative of recent and old infections in afflicted patients and controls[1],[2],[4]. This observation is also indicative of a persistent infection characterized by sequestration of the virus in P antigen rich tissues/organs such as the liver, myocardium, bone marrow and endothelium coupled with a possibility of a viremia below the detection threshold of the PCR method used[1],[2],[4],[24],[25]. These scenarios have also been reported in similar studies from other SCA endemic countries.…”
Section: Discussionmentioning
confidence: 96%
“…This temporary halt in the production of red blood cells occurs only in patients with chronic hemolytic anemia due to the short lifespan of red blood cells. The risk of B19 transmission increases in these patients ( 5 , 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…After reviewing the literature and reported cases, we found that usually the infection occur during childhood or early adolescence. The peak incidence rates occur in 6 to 14-year-old [5] , but rarely during adulthood. Parvovirus infection causes transient aplastic crisis in patients with hemolytic anemia such as sickle cell anemia, hereditary spherocytosis and thalassemia.…”
Section: Discussion: -mentioning
confidence: 99%
“…Infection is most frequently found in the late winter or early spring. As parvovirus DNA has been found in respiratory secretions at the time of viremia, the most common route of transmission appears to be respiratory [5] .…”
Section: Discussion: -mentioning
confidence: 99%